DAMPAK BERBAGAI ALTERNATIF KEBIJAKAN TERHADAP ARUS PERDAGANGAN LADA PUTIH INDONESIA DI PASAR IMPOR LADA PUTIH DUNIA - -, EDIZAL (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The main objective of this study are the simulation of shifter exogenous variable as changing of demand, price and supply for performance of Indonesian white pepper trading in import market world white pepper. The results of simulation indicate that Singapore is highest responsive to increase demand of Indonesian white pepper, but not followed by price response if increasing 5% demand world white pepper. Increasing of Indonesian white pepper supply 5% to have influence on decreasing 2.4% of price world white pepper. Decreasing import tariff 3% white pepper for Japan and ROW more advantage for Indonesia than decreasing import tariff the same level for USA and European Economy Community.
Keywords: White Pepper, Demand, Supply and Price